2012
DOI: 10.1007/s00540-012-1440-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rocuronium, sugammadex, and their combination on cardiac muscle and diaphragmatic skeletal muscle cells

Abstract: Rocuronium, sugammadex, and rocuronium-sugammadex complexes cause histopathological changes and immunoreactivity to calcineurin in muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…In a similar study, they reported that rocuronium-sugammadex complex caused edema and degeneration in the heart and diaphragm muscle tissues. It has been suggested that the effects may not be directly related to sugammadex, and that the aminosteroid structure of rocuronium may have an effect on myopathy (22). In our study, tissue edema, vessel dilatation and haemorrhagic areas were detected in the histopathological examination of the sugammadex-rocuronium group, but no signs of inflammation or fibrosis were found.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In a similar study, they reported that rocuronium-sugammadex complex caused edema and degeneration in the heart and diaphragm muscle tissues. It has been suggested that the effects may not be directly related to sugammadex, and that the aminosteroid structure of rocuronium may have an effect on myopathy (22). In our study, tissue edema, vessel dilatation and haemorrhagic areas were detected in the histopathological examination of the sugammadex-rocuronium group, but no signs of inflammation or fibrosis were found.…”
Section: Discussioncontrasting
confidence: 48%
“…In this study, the dose of sugammadex that is used safely in humans was used. Although higher doses have been used in some studies, a dose of 16mg/kg has been used in many studies (9,21,22). There was no significant difference found in cardiac and diaphragmatic skeletal muscle with 16 mg/kg and 96 mg/kg sugammadex doses (22).…”
Section: Discussionmentioning
confidence: 99%
“…Tomak et al . used various doses of sugammadex, including 16 mg/kg, 96 mg/kg and 100 mg/kg, in their studies. The beta‐cyclodextrin sulphobutylether‐b‐cyclodextrin (SBE‐CD) was used at 2.25 g/kg dose to treat verapamil toxicity .…”
Section: Discussionmentioning
confidence: 99%
“…The rats were divided into six groups (five study groups and a control group) comprising seven rats in each group. The following appropriate combinations of drugs, which represent the low and high tolerable doses with the desired clinical outcome in rats and human (Cammu et al, 2008;Kalkan et al, 2012aKalkan et al, , 2012bPeeters et al, 2010;Rex et al, 2010), were administered i.v. via caudal vein.…”
Section: Animals and Treatmentmentioning
confidence: 99%